The accused bodybuilder subculture (Academic Journal of Internal Affairs, 2023)
Aim: Due to the widespread of bodybuilding activities and the growing health and economic risks of the open use of performance-enhancing drugs associated with the subculture, criminal law regulation as a social tool became involved in problem management. The study examines the characteristics of law enforcement and the group of offenders.Methodology: The author presents the main results of the criminological scientific research she conducted in 2022, on the entire national sample, using the method of document analysis, on the characteristics of performance-enhancing drug abuse crimes that became known between 2014–2021.Findings: The results of the research indicate that „no one takes seriously” the use of performance-enhancing drugs and its prosecution. By ratifying the signed international agreements, we have ticked off our international obligations, but the frameworks and tools actually required for implementation are missing. The ever-widening global demand for performance-enhancing drugs, fake or prescription drugs, or drugs not authorized in Hungary, and the procurement facilitated by e-commerce, result in the development of an extremely capital-intensive market, which in its dynamics approaches and even matches the drug market. It should be noted that, in addition to body builders and personal trainers, among the offenders, the involvement of the police is significant.Value: The research results give an overview of what kind of offenders and what kind of substance abuse procedures are initiated in Hungary, and also reflect what patterns are typical in the offenses and in judicial practice.
Keywords: body building; performance enhancing drugs; drug counterfeiting